2023
DOI: 10.2147/ppa.s423520
|View full text |Cite
|
Sign up to set email alerts
|

Perception and Attitude of Lebanese IBD Patients During the COVID-19 Pandemic

Elio Mikhael,
Yaacoub Khalife,
Cesar Yaghi
et al.

Abstract: Objective The emergence of the COVID pandemic affected daily living and healthcare access of IBD patients, due to delays of elective procedures and in-hospital treatments. Our aim is to determine the repercussions of the pandemic on the daily habits of IBD patients and on their compliance to follow-up and treatment. Methods This was a cross-sectional observational study. A questionnaire was administered in between 2020 and 2022 to IBD patients in a tertiary center in Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The management of chronically ill patients was greatly affected by the pandemic, given the significant mental and physical impact on their behaviors, attitudes, and perceptions [ 66 , 69 , 70 , 71 ]. This has resulted in an ongoing cycle of stress, depression, and disease activity relapse [ 24 ], along with notably diminished adherence to prescribed medications [ 24 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The management of chronically ill patients was greatly affected by the pandemic, given the significant mental and physical impact on their behaviors, attitudes, and perceptions [ 66 , 69 , 70 , 71 ]. This has resulted in an ongoing cycle of stress, depression, and disease activity relapse [ 24 ], along with notably diminished adherence to prescribed medications [ 24 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have shown that a significant number of patients with IBD have delayed or canceled hospital visits due to fear of contracting COVID-19 [ 71 , 73 ]. In Lebanon, over 50% of patients with IBD in the study delayed hospital treatment [ 71 ], while in Korea, more than half of the patients surveyed canceled or postponed their hospital visits [ 73 ]. However, telemedicine and phone consultations have emerged as viable solutions to ensure that patients with IBD receive the care they need [ 71 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations